Spiritual transcendence and religious practices in recovery from pathological gambling: Reducing pain or enhancing quality of life? - Walsh, James M. (Research in the social scientific study of religion, 2007)
In a sample of pathological gamblers from Gamblers Anonymous and a variety of treatment programs (N = 100), spiritual transcendence and religious experiences have significant and predictive relationships with subjective well-being and attainment of abstinence in persons with a diagnosis of pathological gambling. The five-factor model of personality was used to test whether personality fully mediated the relationships to subjective well-being for spiritual transcendence and religious practices. Spiritual transcendence was assessed using the Spiritual Transcendence Scale and by gathering data describing certain religious practices and experiences. Personality fully mediated the effect of religious practices on subjective well-being, but spiritual experience made a significant independent contribution to both reducing negative affect and increasing cognitive well-being. The incorporation of spiritual and religious constructs into treatment programs may facilitate improvement in recovery from pathological gambling.